Assessment of droughts and wheat yield loss on the North China Plain with an aggregate drought index (ADI) approach. (April 2018) - Wang, Sisi; Mo, Xingguo; Hu, Shi; Liu, Suxia; Liu, Zhengjia
Highlights: An aggregate drought index (ADI) was introduced based on seven widely-used indices. ADI performed a stronger ability to capture drought events. Panel model was used to quantify relationships between yield anomalies and ADI. Irrigation managements had a large impact on yield predictions. Abstract: Frequent drought events are threatening regional/global food security. However, current models for predicting crop yield loss suffered from drought threat is still limited. In this study, seven drought indices were employed to develop an aggregate drought index (ADI) to quantify the drought effect on crop yield in the North China Plain (NCP). Based on time-series and panel regression models, relationships between climatic yield anomalies of winter wheat (ΔY) and ADI values before sowing of winter wheat and during its growth were investigated. Results showed that ADI assembled the advantages of drought indices and reasonably described the range, severity and duration of drought events. During the study period, trends of annual ADI displayed remarkable spatial heterogeneity in the growth stages. Increasing trends of ADI over 0.005/year were found in most areas of NCP at STAGE 1 (from July to September in last year). At STAGE 4 (from grain-filling to maturation), increasing and decreasing trends were observed in northern and southern NCP, respectively. Based on panel model, ADI in the four stages could predict about 20% variations of ΔY in areas with high irrigation supplies. Meanwhile, more than 40% variations of ΔY may be predicted in eastern NCP with low irrigation supplies. The study highlights the importance of integrating drought information and irrigation for assessment of winter wheat yield variations.